Cyclic stability of superelasticity in [001]‑oriented quenched Ni44Fe19Ga27Co10 and Ni39Fe19Ga27Co15 single crystals - Timofeeva, Ekaterina E.; Panchenko, Elena Yu; Eftifeeva, Anna S.; Tagiltsev, Anton I.; Surikov, Nikita Yu; Tokhmetova, Aida B.; Yanushonite, Eleonora I.; Zherdeva, Maria V.; Karaman, Ibrahim; Chumlyakov, Yuri I. (Acta metallurgica Sinica (English letters))
The study of the influence of the cobalt content on the cyclic stability of superelasticity (SE) was carried out in quenched Ni44Fe19Ga27Co10 and Ni39Fe19Ga27Co15 (at.%) single crystals under compression. It is shown that an increase in the cobalt content leads to embrittlement of the material and a decrease in the cyclic stability of SE. In Ni44Fe19Ga27Co10 single crystals, during the first 20 loading/unloading cycles, the elastic energy relaxation occurs along with the formation of dislocations and residual martensite, which leads to a decrease in critical stress of martensite formation and in stress hysteresis. During the next 80 cycles, SE becomes more stable. Stabilization is accompanied by a slight change in the parameters. On the contrary, Ni39Fe19Ga27Co15 single crystals are characterized by high-strength characteristics, which lead to high SE stability during the first 20 loading/unloading cycles. However, after 20 cycles, a strong degradation of the SE is observed through the formation of microcracks, which ultimately leads to the destruction of the sample. The results of work are replicable for cycling at different temperatures from all temperature ranges of superelasticity.